Pengaruh Modal, Teknologi, dan Tenaga Kerja Terhadap Produksi dan Pendapatan Usaha Kerajinan Ukiran Kayu di Kecamatan Tembuku Kabupaten Bangli - mahayasa, idabagus adi; Yuliarmi, NI Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 8. Agustus 2017(pp.1395-1627), 2017)
Bangli Regency is one of the districts with the largest number of handicraft industry in the Bali province. one of them is  woodcarving craft. The propose of this study are to know : 1) the influence of capital, technology, and labor toward production craft of wood carving. 2) to know that the moderating influence of the technology work force against productioncraft of wood carving. 3) to analyze the effect of capital, labor, and the production of income. 4) to know that mediate the influence of capital, production and labor against the income of the craft of wood carving in  Tembuku district. this study used  observation and indepth interview with the craftsmen metods. Analytical techniques used IE path/path analysis engineering analysis and test of sobel analyze the effect of indirectly throught intervening variables. The result of this study are Capital and labor have  positive and significant effect against the income. Labor and capital have indirectly iffect again the income. The variable technologies are not capable of moderating influence among labor against production because this technology can be called as the independent variables, which means that this technology is directly against the influential production without going through labor. Advice from research is the role of Government in strengthening this craft businesscapitalization and the us of appropriate technology is crucial to increasing the revenue received by the craftsmens effort can occur so it will affect its economy.
Keywords: Modal,Teknologi,Tenaga Kerja,Produksi,Pendapatan